Ceramic materials characterization using miniature mechanical tests: comparison between B3B and SPT tests. Issue 14 (November 2019) - Quintana, C.; Rodríguez, C.; Belzunce, F.J.; Caballero, A.C.; Baudín, C.
Abstract: Strength of ceramic components is determined by processing, therefore, test methods that allow analysing their actual mechanical behaviour are needed. The miniature mechanical tests ballon three balls (B3B) and small punch (SPT) are compared using commercial lead zirconate titanate (PZT) piezo-ceramic discs. The Weibull distributions of strength were obtained and the fracture surfaces were observed by scanning electron microscopy. The different approaches for the calculation of strength values are discussed. The adequacy of the small punch test for the determination of strength is demonstrated. Results for SPT and B3B tests are comparable considering the effective volumes calculated using the Weibull relationships. The Timoshenko equation for strength is proposed for the calculus of strength due to its simplicity and the fact that the calculated values for B3B and SPT geometries are not dependent on the radius of the uniform loading central area.